Pemetaaan Pengetahuan Guru Biologi dalam Menerapkan Kerangka Pembelajaran Technology Pedagogical Content Knowledge (TPACK) di SMA Negeri Se-Kota Palu - Kasim, Amirudddin; Tellu, Andi Tanra; Laenggeng, Abd Hakim; Nurdin, Musdalifah (Jurnal Kreatif Online, 2020)
This study aims to map the knowledge of biology teachers about the use of the Technological Pedagogical Content Knowledge (TPACK) learning framework in public high schools in Palu city. The intention of this study was that the steps and policies can be formulated regarding the use of the TPACK learning framework. By doing so, teachers can present interesting learning for students thus they are motivated to take part in learning biology which in turn can improve their learning outcomes. TPACK is a learning framework that combines technology, pedagogy and learning material content. The research method used descriptive exploratory. The sampling technique was purposive sampling. The data were collected using questionnaire distribution that was given to high school biology teachers across 10 public high schools in Palu city with the total of 21 respondents. The data analysis used descriptive percentage. The results showed that the knowledge of biology teachers at SMA Negeri Palu was 54.3% in the criteria of â€œknowing enoughâ€ about the implementation of the TPACK learning framework.